Circuito agroturístico y cultivos tradicionales en la Cooperativa de Producción y Comercialización la Clementina, trabajadores propietarios (COOPROCLEM), parroquia La Unión – cantón Babahoyo – provincia de los Ríos - Avila Alvarado, Leonela María (2018)
Ecuador, despite its small size, is one of the 17 most mega-diverse countries in the world, due to its geographical location it has a variety of ecosystems filled with countless species of flora and fauna in its four regions (Costa , Sierra, Amazon and Galápagos) with different climatic floors. In the Province of Los Ríos belonging to the coast, with a tropical climate we have the largest Hacienda in Ecuador '' La Clementina '' which has an extension of 9,600 hectares, in which they are mainly engaged in agricultural production in crops such as; banana, coffee, lemon, teak, among others. This project, carried out at La Hacienda La Clementina, which is fundamental for its development, has as its main objective to draw up an agrotourism circuit to take advantage of traditional crops for tourism purposes, in the La Unión Parish - Babahoyo Canton - Province of Los Ríos. Its purpose is to design the agrotourism circuit to benefit the population, improving the growth of tourism and the economic development of this sector, promoting sustainable development, strengthening and full citizen participation in peaceful coexistence and harmony with nature, without to compromise and guarantee the quality of life of future generations.